Conversion rates of an interferon-γ release assay and the tuberculin skin test in the serial monitoring of healthcare workers - Kim, S. Y.; Park, M. S.; Kim, Y. S.; Kim, S. K.; Chang, J.; Kang, Y. A. (Infection, 2013)
Purpose Regular monitoring of latent tuberculosis (TB) infection in healthcare workers (HCWs) is recommended, but the view about the effective method and performance of serial monitoring is controversial. The aim of this study was to determine differences in conversion rates according to TB exposure risk using the tuberculin skin test (TST) and the QuantiFERON-TB Gold In-Tube (QFT-GIT), and to evaluate the reproducibility and within-subject variability of the QFT-GIT in South Korea. Methods Fifty-three HCWs were grouped according to their risk for TB exposure: group 1, high risk ( n = 21); group 2, low risk ( n = 32). Baseline and follow-up TSTs and QFT-GITs were performed from June 2009 to July 2011. Enzyme-linked immunosorbent assays (ELISAs) were repeated for the second QFT-GIT and a third QFT-GIT was performed after 8 weeks when discordant results of the second TST and QFT-GIT or a conversion or reversion were observed. Results No difference in the QFT-GIT conversion rate was evident between the two groups (15.4 vs. 6.5 %, p = 0.57), and no TST conversion was observed. The rate of QFT-GIT positivity was higher in the high-risk group (first QFT-GIT: 38.1 vs. 3.1 %, p = 0.002; second QFT-GIT: 33.3 vs. 9.4 %, p = 0.039). The re-test reproducibility of QFT-GIT results was high (100 %), and the within-subject results of repetitive QFT-GITs were variable. Conclusions Stricter prevention strategies remain necessary in HCWs at high risk of TB exposure, and serial interferon-γ release assays (IGRAs) should be interpreted with caution in HCWs.